Let’s stay connected: The impact of social and business networks on foreign subsidiary performance - Valentino, Alfredo; Mayrhofer, Ulrike; Caroli, Matteo (Management international / International Management / Gestiòn Internacional, 2022)
Using the extended resource-based view and the network approach, this paper investigates the impact of social and business networks on the performance of foreign subsidiaries. The empirical study is based on a sample of 120 subsidiaries established by multinational enterprises in Italy. Our findings show that social networks have a positive effect on the performance of subsidiaries through the mediating role of business networks. Our research challenges extant literature on the network-performance relationship and highlights the necessity to provide more importance to the way local subsidiaries manage their networks.